Kinetics of Insoluble Cellulose Fermentation by Continuous Cultures of Ruminococcus albus - Pavlostathis, Spyros G. (1988)
Data from analyses of continuous culture fermentation of insoluble cellulose by Ruminococcus albus 7 were used to derive constants for the rate of cellulose hydrolysis and fermentation, growth yield, and maintenance. Cellulose concentration was 1% in the nutrient reservoir, and hydraulic retention times of 0.5, 1.0, 1.5, 1.75, and 2.0 days were used. Concentrations of reducing sugars in the cultures were negligible (less than 1%) compared with the amount of hydrolyzed cellulose, indicating that cellulose hydrolysis was the rate-limiting step of the fermentation. The rate of utilization of cellulose depended on the steady-state concentration of cellulose and was first order with a rate constant (k) of 1.18 day(−1). The true microbial growth yield (Y) was 0.11 g g(−1), the maintenance coefficient (m) was 0.10 g g(−1) h(−1), and the maximum Y(ATP) was 7.7 g of biomass (dry weight) mol of ATP(−1).